2016
DOI: 10.1111/jir.12336
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and screening in persons with an intellectual disability living in institutions in France

Abstract: The results of this study show that BC is equally as frequent among women with ID living in institutions as in the general population, and occurs at around the same age. Obesity was significantly more frequent among women in whom BC was diagnosed in our study. Participation in BC screening is slightly higher among women with ID living in institutions than among the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…6 A Canadian study demonstrated a low uptake of cancer screening among adults with intellectual and development disabilities. 7,8 One report from France on women with an intellectual disability living in institutions found participation in breast cancer screening to be slightly higher than among the general population (64.4% vs. 62% respectively), 3 but another found a low cervical cancer screening rate amongst women living in institutions in France. 9 A review on colorectal cancer in people with intellectual disabilities concluded that, although this group has a risk of colorectal cancer comparable with the general population, their uptake of screening is lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A Canadian study demonstrated a low uptake of cancer screening among adults with intellectual and development disabilities. 7,8 One report from France on women with an intellectual disability living in institutions found participation in breast cancer screening to be slightly higher than among the general population (64.4% vs. 62% respectively), 3 but another found a low cervical cancer screening rate amongst women living in institutions in France. 9 A review on colorectal cancer in people with intellectual disabilities concluded that, although this group has a risk of colorectal cancer comparable with the general population, their uptake of screening is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Although their cancer risk equals that of the general population. 3,4 The objective of this study was to explore the association between different disabilities and participation in cancer screening in Flanders.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our results, a few previous studies have found considerably lower participation in breast cancer screening among women with ID compared with women without ID. The proportions of participation differ widely across studies (4%-64%), [8][9][10][11][12][13][14][15] and comparison of results are challenging.…”
Section: Discussionmentioning
confidence: 99%
“…First, the studies were conducted in Taiwan, 11 Australia, 9 France, 12 the US, 8,13 Canada, 14 and South Korea, 10 where the health care systems, screening programs, and access to cancer screening differ widely. Second, various definitions of screening participation were applied.…”
Section: Discussionmentioning
confidence: 99%
“…People with intellectual disabilities experience higher levels of obesity, with fewer than 10% of individuals residing in supported accommodation, eating a balanced diet, and less than 20% meeting the UK government guidance level for physical activity (Emerson, Baines, Allerton, & Welch, ). A French study also showed that women with intellectual disabilities , who developed breast cancer were twice as likely to be obese, than those who had not contracted the disease (Trétarre et al., ). However, fewer people with intellectual disabilities smoke or drink alcohol than the general population (Emerson et al., ).…”
Section: Introductionmentioning
confidence: 99%